Jasmonate regulates plant resistance to Pectobacterium brasiliense by inducing indole glucosinolate biosynthesis - Yi, So Young; Lee, Myungjin; Park, Sun Kyu; Lu, Lu; Lee, Gisuk; Kim, Sang-Gyu; Kang, Si-Yong; Lim, Yong Pyo (Frontiers in Plant Science, 2022)
Pectobacterium brasiliense (P. brasiliense) is a necrotrophic bacterium that causes the soft rot disease in Brassica rapa. However, the mechanisms underlying plant immune responses against necrotrophic bacterial pathogens with a broad host range are still not well understood. Using a flg22-triggered seedling growth inhibition (SGI) assay with 455 Brassica rapa inbred lines, we selected six B. rapa flagellin-insensitive lines (Brfin2-7) and three B. rapa flagellin-sensitive lines (Brfs1-3). Brfin lines showed compromised flg22-induced immune responses (oxidative burst, mitogen-activated protein kinase (MAPK) activation, and seedling growth inhibition) compared to the control line R-o-10; nevertheless, they were resistant to P. brasiliense. To explain this, we analyzed the phytohormone content and found that most Brfin lines had higher P. brasiliense-induced jasmonic acid (JA) than Brfs lines. Moreover, MeJA pretreatment enhanced the resistance of B. rapa to P. brasiliense. To explain the correlation between the resistance of Brfin lines to P. brasiliense and activated JA signaling, we analyzed pathogen-induced glucosinolate (GS) content in B. rapa. Notably, in Brfin7, the neoglucobrassicin (NGBS) content among indole glucosinolates (IGS) was significantly higher than that in Brfs2 following P. brasiliense inoculation and genes involved in IGSs biosynthesis were also highly expressed. Furthermore, almost all Brfin lines with high JA levels and resistance to P. brasiliense had higher P. brasiliense-induced NGBS levels than Brfs lines. Thus, our results show that activated JA-mediated signaling attenuates flg22-triggered immunity but enhances resistance to P. brasiliense by inducing indole glucosinolate biosynthesis in Brassica rapa. This study provides novel insights into the role of JA-mediated defense against necrotrophic bacterial pathogens within a broad host range.